Kedudukan Perempuan sebagai Mamak Kepala Hindu di Kel. Tiakar Kec. Payakumbuh Timur Menurut Pandangan Maqashid Syariah - Rafifah Diva Helsya; Gusril Basir (AHKAM, 2026)
Women’s leadership in customary structures remains a debated issue in society, including in the context of ancestral property management among the Minangkabau community. Mamak kepala waris is an informal figure within a clan who is responsible for managing the distribution of ancestral property and various matters related to the clan’s inheritance, with the appointment process based on the agreement of clan members, either directly or implicitly. This study aimed to analyze the position of women as mamak kepala waris in Tiakar Urban Village and to examine this role from the perspective of Maqashid Syariah. This study used a descriptive qualitative approach with a field research design. Data were collected through observation and interviews with relevant informants and then analyzed descriptively and qualitatively. The results showed that the position of women as mamak kepala waris had been customarily recognized through a clan agreement letter and supported by the Kerapatan Adat Nagari, and was also in line with the Supreme Court decision. From the perspective of Maqashid Syariah, women’s leadership in customary structures can be accepted if it fulfills the five objectives of sharia, namely preserving religion, intellect, life, lineage, and property. The conclusion of this study emphasizes that Minangkabau women have an important position and contribution in customary structures, particularly in the management and preservation of the clan’s harta pusaka tinggi. These findings imply the strengthening of understanding regarding the flexibility of customary leadership based on clan agreement and its relevance to the principle of public benefit in Maqashid Syariah.